Research of electro-physical and operating properties of polyorganosiloxane – graphite compositions - Мельник, Любов Іванівна; Мелконян, Арегназ Арменівна; Деренговський, Андрій Валерійович (Technology audit and production reserves, 2016)
This article is devoted to solving scientific and practical problem - the development of new siloxane graphite conductive composite materials with adjustable electrical properties and high thermal stability. Such compositions can be used as heating devices in some premises for different purposes, heating shoes, anti-icicle mean. The results of research of electrical conductivity for system polyorganosiloxane- filler in a wide concentration range of the last and impact of ethyl silicate-40 on its shift. It is established that the experimental compositions based on polyorganosiloxane graphite system GLS-1 have percolation effect within 32-35 weight % of graphite, coating electrical resistivity abruptly dropped to a level of 165∙10-3 Ohm∙m. Increasing the concentration of graphite to 60 weight % leads to a further reduction in resistivity to a level of 90∙10-3 Ohm∙m. The most significant decrease in electrical resistivity in the system PMFS-GLS-1 is achieved at injection of additional 5 weight % of ethyl silicate-40 with further heat treatment followed by 3 hours at 250 °C. The value of this index does not exceed 30∙10-3 Ohm∙m. The test systems are characterized by a negative temperature coefficient of resistance over wide concentration range of the filler and have high adhesion ability to substrates of different nature. There are hydrophobic coatings. Filler concentration significantly affects the electrical properties of the composition, so the dependence of power density of filler content (at almost the same temperature of heating surface) is parabolic in nature with minimal filler concentrations in the range 55...60 weight %, regardless of the nature of binding and for system PMFS-GLS-1 in the temperature range 175...185 °C at a concentration of 31,5-55-76 weight % specific power is under 0,718-0,639-0,997 W/cm2, and PFS-GLS in the temperature range 170...195 °C and concentration of 30-60-70 weight % it is under 0,938-0,530-0,927 W/cm2. The behavior of these systems as heating elements is studied. A one possible heater construction form developed compositions is proposed. Its performance characteristics are studied.